REFLEXIONES EN EL ANIVERSARIO DE PLAYA GIRÓN: CADA ESCUELA UNA FORTALEZA DE LA REVOLUCIÓN - Pérez Cruz, Felipe (2012)
To highlight the role of Fidel’s historical personality in school events and literacy forms the basis for the validity of considering him a pedagogue of the Revolution, as has certainly been catalogued by Paulo Freire (Freire and others, 1997, p. 14).With such definition, the illustrious Brazilian philosopher was not only making reference to the contributions he attributed to the Cuban leader specifically in the educational field.  He was also including the understanding of the Gramscian conception (22) on the role of education as a device of construction of hegemony at the center of civil society, the accurate idea of the Italian Marxist theorem about the consideration of the eminently pedagogical character of relationship, which assumes class struggle in the ideological cultural field.  This matrix concept, made praxis of success by the Commander in Chief Fidel Castro Rux, is one of his most timeless legacies. The rise of the educational work to the plane of a struggle for the defense of the Revolution occurs not only through the will of some or other revolutionary leaders; it transcends the disposition of ministries and governmental institutes.  It struggles and presents itself in the construction and mounting development of a solid and massive educational movement of the masses.  We can never forget this historical truth.